Runaway electron mitigation by 3D fields application in ASDEX Upgrade, COMPASS, and RFX-mod - Gobbin, M.; Valisa, M.; Marrelli, L.; Papp, G.; Pautasso, G.; Tomesova, E.; Markovic, T.; Ficker, O.; Cerovsky, J.; Liu, Y.; Li, L. (Frontiers in Physics, 2024)
The disruption generated runaway electron (RE) beams represent a potentially severe threat for the tokamak plasma-facing components. Application of properly designed 3D fields can act as a mitigation mechanism, as recently investigated in ASDEX Upgrade (AUG) and COMPASS experiments and in the tokamak discharges of RFX-mod. In all of these devices the dynamics of the disruption are affected by the application of magnetic perturbations (MPs), and the resulting RE beam current and lifetime are significantly reduced. These experiments show in particular that the strength of the observed effects strongly depends on the poloidal spectrum of the applied MPs, which has been reconstructed including the plasma response. This paper reports the main findings on RE mitigation from the three devices highlighting the common physics which is behind them and their interpretation by using the guiding center code ORBIT.